Selection for the Timing of Adult Emergence Leads to Evolution in the Molecular Circadian Clock and Its Light Input Pathway in Drosophila melanogaster Populations. - Balaji, A.; Sreelakhsmi, E.H.; Kannan, N.N. (Journal of Biological Rhythms, 2026)
The light input pathways and the molecular clock are tightly linked, with light serving as the most potent zeitgeber that entrains the clock to the external environment. Our present study focuses on the Drosophila melanogaster populations that have evolved with a precise circadian clock as a correlated response to selection for adult emergence in a narrow window of time over 335 generations. The results of our study showed that flies from populations selected for the timing of adult emergence sleep more during the night phase compared to controls. This sleep was even more enhanced when the light intensity was reduced to 1 lux under a 12 h light:12 h dark cycle. In addition, a significantly higher percentage of these flies exhibited free-running period rather than arrhythmicity compared to the control flies under constant light (1 lux). Moreover, the larvae from selected populations exhibited an increased preference toward darkness than light indicating that the effect of selection extends beyond the adult circadian light input pathway, influencing the innate circadian regulated photobehavior in larvae. We examined the transcript oscillation of the circadian photoreceptor cryptochrome (cry), along with the core clock genes period (per) and timeless (tim) in adult flies to explore the molecular basis of the evolved precise circadian clocks and to determine whether selection influences the circadian light input pathway. Flies from the selected population exhibited a phase advance in the transcript oscillation of per, tim, and cry, indicating that the molecular circadian clock and its light input pathway evolve as a correlated response to the selection for the timing of adult emergence in D. melanogaster populations.